2014
DOI: 10.1002/biot.201300507
|View full text |Cite
|
Sign up to set email alerts
|

Microbubble‐mediated sonoporation for highly efficient transfection of recalcitrant human B‐ cell lines

Abstract: Sonoporation has not been widely explored as a strategy for the transfection of heterologous genes into notoriously difficult-to-transfect mammalian cell lines such as B cells. This technology utilizes ultrasound to create transient pores in the cell membrane, thus allowing the uptake of extraneous DNA into eukaryotic and prokaryotic cells, which is further enhanced by cationic microbubbles. This study investigates the use of sonoporation to deliver a plasmid encoding green fluorescent protein (GFP) into three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Cell monolayers can give insight into cell viability, gene transfection, and drug uptake [107]. For example, Yong et al have shown an increase of 42% genre transfection rate in B-cell lines over conventional transfection using cell monolayers [109].…”
Section: Microfluidic Chips To Study Mb/cell Interactionsmentioning
confidence: 99%
“…Cell monolayers can give insight into cell viability, gene transfection, and drug uptake [107]. For example, Yong et al have shown an increase of 42% genre transfection rate in B-cell lines over conventional transfection using cell monolayers [109].…”
Section: Microfluidic Chips To Study Mb/cell Interactionsmentioning
confidence: 99%
“…Sonoporation, for example, involves the use of ultrasound to cause a temporary increase in cell membrane permeability through the creation of pores, allowing the intracellular diffusion of macromolecules such as DNA (Fan et al, 2014). Sonoporation has recently been described for high-efficiency transfection of B cells (Ling Yong et al, 2014) and has been employed to increase in vivo delivery of a DNA vaccines to APCs. Using ultrasound (US)-responsive and APC-selective lipolex capsules to carry plasmid DNA, this targeted delivery approach was found to generate potent and sustained effects against solid and metastatic melanomas (Un et al, 2011).…”
Section: Dna Vaccines – Mechanisms Of Action; Increasing Immunogenmentioning
confidence: 99%
“…20,38 Using the same monolayer model, enhanced gene transfection has been reported more recently for human B-cell lines using plasmid-coated microbubbles, which were activated by ultrasound. 41 Monolayers formed from endothelial cells can act as artificial blood vessels, and implementing them in a microchannel format allows studying flow-based delivery of microbubbles and recapitulating physiologically relevant cellular shear stress, as would occur in vivo. 42 Alternatively, cell population studies rely on the use of suspended cells.…”
Section: Cell Populations: Monolayer Models and Suspended Cellsmentioning
confidence: 99%